Spatio-temporal distribution patterns and risk assessment of microplastics along a coastal beach in southern Bangladesh - Md. Shawon Hossain; Kowshik Das Karmaker; Mahfujur Rahman; Arnob Ghosh; Swachsa Rahman; Shamiha Shafinaz Shreya; Jarin Tasnim; Mahir Tajwar; Nusrat Jahan Shimu; Mahmud Al Noor Tushar; Mir Shariful Islam; Mohammad Abdul Momin Siddique; et al. (Marine Pollution Bulletin, 2026)

Prevalence and cow-level risk factors for mild and severe subclinical mastitis in intensive and extensive dairy systems in Bangladesh - Muhammad Aktaruzzaman; M. Ariful Islam; Solama Akter Shanta; Mst. Tahomina Akter; Muhammad Tofazzal Hossain; Md. Nazmul Islam; Md. Shaffiul Alam; A. K. M. Anisur Rahman (Veterinary Research Communications, 2026)

Monitoring Extent of Mangroves in Coastal Bangladesh from 1980 to 2020: A Remote Sensing-Based Geospatial Analysis - Muhammad Al-Amin Hoque; Maliha Sanzana Misty; Khandaker Tanvir Hossain; Sharif A. Mukul (Small-scale Forestry, 2026)
Mangrove ecosystems play a vital role in coastal protection, biodiversity conservation, and climate regulation, yet their spatiotemporal dynamics within highly geomorphologically active deltaic environments remain insufficiently understood. This study aimed to map long-term changes in mangrove distribution, quantify mangrove gain and loss patterns, identify dominant land-cover transition pathways, and evaluate the influence of erosion–accretion processes on mangrove dynamics in the Meghna Estuary of coastal Bangladesh using a remote sensing-based geospatial framework spanning 1980–2020. Multi-temporal Landsat imagery was processed through standardized pre-processing, NDVI analysis, and supervised Maximum Likelihood land-use/land-cover classification to quantify mangrove extent, spatial trajectories, and gain–loss dynamics. Post-classification change detection and trajectory analysis were employed to evaluate transitions between mangrove, waterbody, vegetation, and agricultural classes. Results reveal a highly dynamic coastal system characterized by alternating phases of mangrove expansion and contraction primarily driven by erosion–accretion processes. Mangrove cover exhibited a net increase of 158.9 km 2 over four decades, with major gains occurred during 1990–1995 and 2000–2005, primarily due to sediment deposition and natural colonization on newly formed mudflats. Conversely, notable declines between 2005 and 2016 were associated with shoreline erosion and channel migration. Land-trajectory analysis highlights dominant waterbody-to-mangrove transitions, emphasizing the importance of geomorphological processes in shaping ecosystem regeneration and resilience. Despite overall expansion, continuous spatial redistribution indicates ecosystem fragility, with gains concentrated on accretion-prone surfaces and losses along erosion-prone margins. The findings provide the first comprehensive four-decade spatial assessment of mangrove dynamics in the Meghna Estuary, offering critical evidence for adaptive coastal management, ecosystem restoration, and nature-based climate mitigation in Bangladesh.

Genomic and phenotypic insights into the probiotic and antimicrobial potential of Bacillus amyloliquefaciens BCSIR-AJ strain from garlic chutney - Mohammed Ayaz; Md Murshed Hasan Sarkar; Mohammad Monerul Islam; Muhammad Irfanul Islam; Farjana Akter Koly; Md. Rakibul Hasan; Md Saddam Hossain; Saiful Islam (Archives of Microbiology, 2026)

Modeling sporadic Alzheimer’s disease using brain organoids: Emerging trends and translational opportunities - Muhammad Kamal Hossain; Hyung-Ryong Kim (Tissue and Cell, 2026)

Pesticides-induced histopathological and biochemical alterations in fish: Impacts and restoration strategies - Shariqul Islam; Muhammad Sohail; Md. Fazle Rohani; Shahadat Hossain; S.M. Majharul Islam (Science of The Total Environment, 2026)

Interlinking behaviour, technology, and roles in women rice seed producer groups of Bangladesh - Swati Nayak; Muhammad Ashraful Habib; Subhasmita Mohapatra; Saidul Islam; Sk Mosharaf Hossain (Next Research, 2026)

From lake to plate: microplastic occurrence in freshwater fish and multi-index assessment of human exposure in Kaptai Lake, Bangladesh - Mohammed Manik; Md. Rashedul Haque; Md. Tauhid Hossain; Wahida Ahmed; Md. Rasheduzzaman; Md. Mostafizur Rahman; Muhammad Aslam Ali; Paolo Pastorino (Food Control, 2026)

Community benefit agreement preferences for energy development offshore California, Oregon, and Washington: Insights from a choice-based conjoint experiment - Hossain Ahmed Taufiq; Gregory Joseph Stelmach; Umama Rahman; Muhammad Usman Amin Siddiqi; Hilary Boudet (Energy Policy, 2026)

Invisible Dangers: A Risk Assessment of Cooking Biomass Fuels and Their Trace Element Exposure in Rural Bangladesh - Md. Badiuzzaman Khan; Muhammad Azizal Hoque; Mauro Masiol; Shamsunnahar Setu; Niger Sultana; M. Rafiqul Islam; Mahmud Hossain (Exposure and Health, 2026)

Characteristics and risks of microplastic contamination in marine trash fish from the northern Bay of Bengal: implications for human health and local aquaculture industry - Muhammad Arifur Rahman; Md. Rakibul Hasan; Khadijatul Kubra Riya; Mohammad Abdul Baten Bhuyain; Sanjida Afrin Semme; Norhayati Ngah; Takaomi Arai; M. Belal Hossain (ENGINEERING Environment, 2026)

Use selenium-doped TiO2 single-wall carbon nanotubes as promoter of biochemical indices in Solanum lycopersicum L. under bacterial wilt stress conditions - Asif Kamal; Akhtar Munir; Khizar Hayat Khan; Ulfat Ara; SK Safdar Hossain; Abdulrazak J. Otaru; Muhammad Tahir Amin; Hayat Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

In silico identification of novel PTP1B inhibitors by the investigation of molecular mechanism, QSAR, and DFT studies - Humaira Zulfiqar; Samira Akter; Jarin Tasnim; Muhammad Younis; Md. Mehedi Hasan; Sidra Manzoor; Sarnop Sarker; Muhammad Waqas; Khan Rajib Hossain (In Silico Pharmacology, 2026)
Protein tyrosine phosphatase 1B (PTP1B) is a well-known and promising drug target involved in the negative regulation of insulin and leptin signaling, and new anti-diabetic molecules for the treatment of type 2 diabetes are directly in its hands. A series of PTP1B inhibitors was discovered and characterized using in silico techniques, including virtual screening, molecular docking, ADMET profiling, toxicity prediction, VEGA-QSAR analysis, molecular dynamics (MD) simulation, and density functional theory (DFT) calculations. A starting library of 1000 anti-diabetic compounds was screened, and PubChem CID 44560696 was identified as the most successful hit. The most potent inhibitor was then identified as CID 44560744 through chemical analogy-based refinement, with a binding free energy of − 9.13 kcal/mol and the ability to form several stabilizing hydrogen bonds and hydrophobic interactions with the key catalytic residues. DFT-optimized geometry and docking revealed that the lead compound shows high stability and strong PTP1B inhibition, showing superior binding affinity compared to ursolic acid, which exhibited a lower binding energy of − 6.34 kcal mol −1 . The MD simulations showed that the PTP1B-ligand complex was structurally stable and compacted during the 200 ns simulation, with desirable profiles for RMSD, RMSF, Rg, SASA, and hydrogen bonds. The DFT and FMO analyses indicated that the compound exhibits extreme chemical reactivity and electron-transfer capability, owing to its low HOMO-LUMO gap, high softness, and moderate electrophilicity. The results of ADMET and toxicity evaluations (SwissADME, ProTox-II, and VEGA-QSAR) pointed to satisfactory solubility, non-carcinogenicity, no mutagenicity, and high pharmacological safety. Overall, the synergy of the computational methods has made CID 44560744 a lead scaffold for the development and optimization of selective PTP1B inhibitors for T2DM therapy.

All-day freshwater generation via low voltage Joule heating–assisted interfacial solar steam generation - Shakeelur Raheman AR; Higgins M. Wilson; Muhammad Nobi Hossain; Sang Joon Lee (Desalination, 2026)

Insight into diving behaviour of the dynamically installed maverick anchor linking to yield surface - Junsik Bae; Muhammad Shazzad Hossain; Youngho Kim (Computers and Geotechnics, 2026)

Host-derived Probiotics Enhance Immune Response and Gut Microbiome in the Freshwater Prawn Macrobrachium rosenbergii - Ayesha Akhter Sumona; Md. Belal Hossen; Saima Binte Hadi; Md. Amdadul Haque; Md. Nurul Haider; Muhammad Tofazzal Hossain; Md Samsul Alam (Probiotics and Antimicrobial Proteins, 2026)

Sewage Sludge-Mediated Microplastic Transfer to Agroecosystem: A Comprehensive Review on Detection, Fate and Ecological Impacts - Muhammad Tariq Khan; Masroor Waliullah; Zohaib Abbas; Saba Hafeez; Mohammad Bhuyan; Nasrin Akhter; Iqbal Ahmad; Asim Nawab; Mushtaq Ahmad; Yanbo Zhou; Md Faysal Hossain (Water, Air, & Soil Pollution, 2026)
Microplastic (MP) pollution has become a significant environmental concern due to its persistent nature and toxic environmental effects. MPs pose threats to the aquatic and terrestrial environment by impacting plant habitats and altering soil properties. Wastewater treatment plants (WWTPs) are one of the most prominent channels for MP pollution in both aquatic and terrestrial ecosystems. MP particles separated during various treatment processes are trapped in the sludge and subsequently enter the terrestrial agroecosystem when sludge is used as fertilizer. In addition, sludge incineration releases tiny MP particles into the atmosphere. Although MPs have been extensively studied in aquatic environments, limited studies are available regarding their transport to agricultural ecosystems and the pathways through which they pose risk to food security and soil fertility. This review aims to evaluate the prevalence of MPs within sewage sludge and their subsequent translocation into terrestrial agroecosystems. A critical investigation has been carried out to address the challenges in detecting MPs in complex sludge samples to provide guidance for developing standardized and widely accepted methodologies. Furthermore, the impacts of MPs on soil fertility and biota were assessed and investigated from the perspective of agricultural production. This review aims to compile evidence of the presence and transport of MPs through sewage sludge applied to agricultural lands and help policymakers and environmentalists in developing viable strategies to protect agricultural land from MP pollution. Graphical Abstract

Impaired Glymphatic Function and Post-stroke Cognitive Decline after Intracerebral Hemorrhage: A Serial Neuroimaging Study - Nina H. Nariman; Md Faruk Hossain; Khader M. Hasan; Vahed Maroufy; Seth B. Boren; Spencer Solberg; Robert Suchting; Clark Sitton; Sean I. Savitz; Muhammad E. Haque (Translational Stroke Research, 2026)

Nitrogen and Phosphorus Deficiency Coordinate Stomatal Closure and Disrupt Leaf Thermoregulation and Stress Metabolism in Rice Seedlings - Mohammad Saidur Rhaman; Md. Asadulla Al Galib; Faruk Hossain Khan; Bir Jahangir Shirazy; Yanjie Xie; Muhammad Farooq; Marian Brestic; Yoshiyuki Murata (Journal of Soil Science and Plant Nutrition, 2026)

Corrigendum to “Predicting blue carbon sequestration in Sundarban coastal mangroves: A spatially explicit approach with INVEST and machine learning to advance climate resilience and UN SDG-aligned nature-based climate solutions” [Mar. Pollut. Bull. 226 (2026) 119387] - Ismail Mondal; SK Ariful Hossain; Muhammad Tauhidur Rahman; Wafeek Mohamed Ibrahim; Mukhiddin Juliev (Marine Pollution Bulletin, 2026)

Predicting blue carbon sequestration in Sundarban coastal mangroves: A spatially explicit approach with INVEST and machine learning to advance climate resilience and UN SDG-aligned nature-based climate solutions - Ismail Mondal; SK Ariful Hossain; Muhammad Tauhidur Rahman; Wafeek Mohamed Ibrahim; Mukhiddin Juliev (Marine Pollution Bulletin, 2026)

Functional, genomic, and transcriptomic insights into linear low-density polyethylene (LLDPE) biodegradation by landfill-derived Brucella intermedia - Ifthikhar Zaman; Mahdi Muhammad Moosa; M. Mahboob Hossain (Journal of Hazardous Materials, 2026)

Antibiotic resistance pattern and molecular study of foodborne pathogenic bacteria isolated from Poultry meat in Bangladesh - Shahin Mahmud; Muhammad Wasim; Md. Firoz Ali; Md. Omar Faruque; Sourav Sarker; Md. Rayhan Ali; Ashraf Hossain Talukder; A.K.M. Mohiuddin; Somaresh Kumar Mondal; Shah Adil Ishtiyaq Ahmad (Food and Humanity, 2026)

Amine-appended bimetallic MOF-74 for highly selective and energy-efficient CO₂ capture under vacuum swing adsorption - Rodynah A. Alabdulhadi; Shabnam Khan; Md Delowar Hossain; Aamir Hanif; Mohammed Ahmed Sanhoob; Mohd Yusuf Khan; Mosim Ansari; Aasif Khan; Muhammad Usman; Saleh AlMansour; Aasif Helal (Chemical Engineering Journal, 2026)

Anxiolytic-like effects of p-coumaric acid via GABAergic interaction pathways: an in vivo and in silico study - Madhu Sah; Balaram Das; Ramesh Kumar Mandal; Raihan Chowdhury; Mohammad Y. Alshahrani; Muhammad Ali Khan; Anik Kumar Saha; U Ching Aoung Chak; Sadia Akhter; Md. Fazla Alahi Nikson; Shama Mohanta; H. M. Shadid Hossain Snigdha; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A comprehensive review of thermal ablation technologies for transdermal drug delivery: mechanisms, commercial products, and future smart systems - Muhammad Murtaza; Salman Ali Khan; Hayat Khan; SK Safdar Hossain (Drug Delivery and Translational Research, 2026)

In-silico screening of anti-cancer natural compounds targeting NF-κB as identification of potential therapeutic inhibitor - Jarin Tasnim; Md. Mehedi Hasan; Qandeel Fatima; Laiba Rashid; Sarnop Sarker; Khan Rajib Hossain; Mamoona Nisar; Md. Tamzid Hossain Molla; Muhammad Imtiaz Shafiq; Mohammad Taufiq Alam (In Silico Pharmacology, 2026)

Three Characterized Probiotics from Dairy Sources—Weissella confusa (ProY 5.1), Enterococcus lactis (ProY 5.3), and Leuconostoc lactis (RM 2.1)—Exhibit Potential for Antidiarrheal Effects - Jannatul Ferdous; Md. Saddam Hossain; Palash Kumar Sarker; Md. Shimul Bhuia; Md. Sakib Al Hasan; Raihan Chowdhury; Md. Sarafat Ali; Md. Robiul Auwal; Keshob Chandra Das; Muhammad Torequl Islam; Abu Hashem; Md. Salimullah (Probiotics and Antimicrobial Proteins, 2026)

Unveiling spatial patterns and drivers of ecological environmental quality change in the exposed coastal zone of Bangladesh - Md. Riyadul Haque; Md Lokman Hossain; Mohammed Abdus Salam; Muhammad Moniruzzaman; Md. Kamruzzaman Tusar; Momotaj Ara Mou; Jianfeng Li; Aishia Fyruz Aishi (Journal of Coastal Conservation, 2026)

Development and evaluation of climate-smart aquaculture interventions to enhance livelihood resilience in salt farming communities of Bangladesh - Md. Rakibul Hasan; Muhammad Meezanur Rahman; Seikh Razibul Islam; Md Anisuzzaman; Khadijatul Kubra Riya; Takaomi Arai; Norhayati Ngah; M. Belal Hossain (Aquaculture International, 2026)

SSGNet: A single-source generalization model for ship detection in UAV imagery under challenging maritime environments - Muhammad Yasir; Shanwei Liu; Mingming Xu; Hui Sheng; Fernando J. Aguilar; Ranyeri do Lago Rocha; Felipe A.P. de Figueiredo; Arife Tugsan Isiacik Colak; Md Sakaouth Hossain (Ocean Engineering, 2026)

Edible mushroom proteins for future foods: Integrative insights into nutrition, technofunctionality, extraction, and safety - Mohamad Ariff Hanafi; Nursyafiqah Mohamad Asri; Shehu Muhammad Auwal; Fatema Hossain Brishti; Nazamid Saari (Food Research International, 2026)

Large-animal farmers’ knowledge, attitudes, and practices regarding antibiotic usage in dairy and beef fattening farms in Bangladesh’s milk pocket areas - Fardina Sultana Sumi; Kazi Rafiq; A. K. M. Anisur Rahman; Muhammad Tofazzal Hossain; Purba Islam; Md. Rakib Hasan; Shah Md. Iqbal; Anan Binte Zaman (Tropical Animal Health and Production, 2026)

Combining anxiolytic activity of thymol and trans-ferulic acid: a potential GABAergic intervention - Md. Hanif Munshi; Noshin Tasnim Yana; Imam Hossen Rakib; Emon Mia; Nusrat Jahan Tohfa; Md. Sakib Al Hasan; Md Abu Sayeed; Mst. Sumaia Akter; Md. Arif Hossain; Muhammad Torequl Islam; Md. Shimul Bhuia; Mushtaq Ahmad Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Habitat suitability analysis for sea cucumber mariculture development in the coastal waters of Bangladesh - Muhammad Mizanur Rahman; Subrata Sarker; Md. Rashed Talukder; Md. Shahadat Hossain; Md. Al Mamun; Tanjida Sultana (International Journal of Remote Sensing, 2026)

Linalool exerts antiemetic effects via dopaminergic and serotonergic pathways: Evidence from chick model and molecular docking - Abdullah Al Fahmi; Khadija Akter; Imam Hossen Rakib; Sakib Hossain; Ali G. Alkhathami; Md. Sakib Al Hasan; Rakib Hossan; Iffat Ara; Md. Mizanur Rahaman; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Linalool (LIN), a naturally occurring monoterpene alcohol found in aromatic plants, exhibits diverse pharmacological properties, yet its antiemetic potential remains underexplored. In this study, we investigated the antiemetic efficacy of LIN using both in vivo and in silico approaches. Emesis was induced in chicks via oral administration of copper sulfate pentahydrate (50 mg/kg), and LIN was tested at doses of 25, 50, and 100 mg/kg. Its effects were compared against the standard antiemetics domperidone (DOM, 7 mg/kg) and ondansetron (OND, 5 mg/kg). Results demonstrated that LIN at 100 mg/kg significantly prolonged the emetic latency and reduced the number of retches. Notably, co-administration of LIN (50 mg/kg) with DOM significantly ( p < 0.05) produced the most potent effect, yielding the highest latency and lowest number of retches, reflecting a synergistic interaction. Molecular docking studies revealed a strong binding affinity of LIN to the dopamine D2 receptor (− 6.4 kcal/mol) and moderate binding to the 5-HT3 receptor (− 5.3 kcal/mol), suggesting involvement of both dopaminergic and serotonergic mechanisms. These findings collectively indicate that LIN possesses significant antiemetic activity and may offer a plant-derived alternative for emesis control.

Enhanced condensation of photoelectrothermally heated vapors using a superhydrophilic surface - Muhammad Nobi Hossain; Younghoon Suh; Sang Joon Lee (Water Research, 2025)

Knowledge, attitude and practices of primary livestock raisers regarding anthrax and anthrax vaccination of livestock in outbreak and non-outbreak areas of Bangladesh - Ireen Sultana Shanta; Kamal Hossain; Syed Sayeem Uddin Ahmed; Melissa Kadzik; Antonio R. Vieira; Taifur Rahman; Rita M. Traxler; Md Saiful Islam; Farhana Haque; Muhammad Belal Hossain; Sk Shaheenur Islam; Nurnabi Ahmed; et al. (Preventive Veterinary Medicine, 2025)

First comprehensive phenolic profiling and antioxidant assessment of red seaweed (Mazzaella japonica) using cold plasma-treated water - Abul Hossain; Muhammad Yasir; Yigong Guo; Anika Singh; David D. Kitts; Anubhav Pratap-Singh (Food Chemistry, 2025)

Mindsets matter: Reimagining the destination brand experience-environmental behaviour link through a cognitive lens - Muhammad I. Hossain; Arnold Japutra; Nurnobi Islam; Ammar Javed (Journal of Environmental Management, 2025)

Dry reforming of methane in molten manganese chloride mixtures - Jimin Lyu; Dohyeon Kim; Muhammad Nobi Hossain; Seongjun Lee; Junyoung Lee; Salh Alhammadi; Minkyu Kim; Dohyung Kang (Chemical Engineering Journal, 2025)

Blue carbon management integrating socioeconomic and environmental interconnectivity in Southeast Asia: an urgent climate priority - Amani Becker; Sarah K. Bercovici; Jenny Choo; Fakhrurrozi Fakhrurrozi; Annabelle Fong; Sara E. Fowell; Emmy Hossain; Muhammad Ali Syed Hussein; Maryam Jamilah; Aazani Mujahid; Moritz Müller; Jillian Lean Sim Ooi; et al. (Frontiers in Marine Science, 2025)
This perspective article synthesises insights from a 2023 interdisciplinary workshop in Kuching, Malaysia, where 26 experts examined how land use and land cover change (LULCC) impacts Blue Carbon Ecosystems (BCE) in Southeast Asia (SEA) and identified pathways for integrated, science-informed governance. BCE in SEA (mangroves, seagrasses and tidal wetlands) are globally significant carbon sinks, critical to biodiversity and the livelihoods of millions, dependant on them for food, income and coastal protection. Yet rapid development and socio-economically driven LULCC threaten BCE resilience and carbon storage capacity. Blue Carbon initiatives risk falling short if they overlook the socio-ecological interconnectivity of these systems. Advances in remote sensing, sediment carbon accounting and ecosystem modelling have improved BCE monitoring, but key gaps persist. These include understanding cumulative upstream effects of LULCC on BCE carbon dynamics, integrating socio-economic with ecological data for robust scenario modelling and evaluating governance effectiveness and equity over time. We frame BCE as dynamic, interconnected socio-ecological systems and call for the advancement of systems thinking in coastal and climate policy. We underscore the need for transdisciplinary, nested governance models operating across ecological scales and political boundaries and argue for a systems-based management approach that links land-sea processes, addresses upstream-downstream dynamics and balances carbon market incentives with local needs. Recommendations include improved monitoring and carbon accounting; alignment between science and policy; regionally coordinated governance; and diversifying finance to reflect the full value of BCE beyond carbon. Together, these actions chart a path for resilient, science-based, socially inclusive BCE conservation in SEA.

Dispersion stability of a water-based ternary hybrid nanofluid with Al2O3, CuO, and graphite: an experimental and RSM modeling approach - Md. Ramim-Ul Hasan; Tanjimur Rashid; Md. Emdadul Hoque; Muhammad Aziz; Md. Sanowar Hossain (Next Research, 2025)

Structure, actors, and interdependencies between informal and formal e-waste management supply chain in Bangladesh - Nasrin Akter; Muhammad I. Hossain (Journal of Cleaner Production, 2025)

All-day desalination and ZLD-oriented brine production using a grass biomass pellet-derived biochar–carbon fabric evaporator - Higgins M. Wilson; Muhammad Nobi Hossain; Shakeelur Raheman A.R; Sang Joon Lee (Chemical Engineering Journal, 2025)

Mechanistic insights into microplastic-induced reproductive toxicity in aquatic organisms: A comprehensive review - A K M Munzurul Hasan; Md. Foysul Hossain; Minhaz Uddin; Muhammad Tariq Khan; Uddin Md Saif; Mohamed Hamed; Christopher J. Martyniuk; Douglas P. Chivers (Aquatic Toxicology, 2025)

Genome-wide Expression of Hsp60 in Anadromous Hilsa Shad (Tenualosa ilisha) during their Downstream Migration across Variable Habitat Temperatures - Md. Toasin Hossain Aunkor; Afroza Pervin; Md. Jubayer Ahmed; Md. Nazmul Hasan; Mohammad Mehedi Hasan Khan; Muhammad Anamul Kabir; Md. Faruque Miah (Thalassas: An International Journal of Marine Sciences, 2025)

The green supply chain conundrum: exploring the interplay of practices, performance, and technology in shaping SME sustainability in developing country - Ikramuddin Junejo; Jan Muhammad Sohu; Aiza Aziz Qureshi; Saba Shaikh; Faisal Ejaz; Tahir Saeed Jagirani; Md Billal Hossain (Environment, Development and Sustainability, 2025)

Prevalence of Low HDL Cholesterol and Its Associated Factors Among Healthy Individuals in Bangladesh: A Cross-Sectional Study on Dyslipidemia and Cardiometabolic Risk - Muhammad Saiedullah; Zimam Mahmud; Md. Omar Faruque; Sonia Tamanna; Md. Zahid Hassan; Md. Zakir Hossain Howlader (Indian Journal of Clinical Biochemistry, 2025)

Multi-strain Native Probiotics from the Asian Stinging Catfish (Heteropneustes fossilis) Enhance Growth, Blood Health, and Organ Morphology in the Host - Sadia Nusrat Sharna; Kaniz Fatema Nur; Atiqur Rahman; Nittyananda Chandra Das; Jesmin Akter; Mst. Halima Khatun; Sara Momtaj Chowdhury; S. M. Majharul Islam; Muhammad Tofazzal Hossain; Mahbubul Pratik Siddique; M Kabir Hossain; Mohd Golam Quader Khan; et al. (Probiotics and Antimicrobial Proteins, 2025)

Anti-arthritic potential of linalool: in vitro, in vivo, and in silico mechanistic insights for safer therapeutic applications - Shoyaeb Ahammed; Raihan Chowdhury; Md. Sakib Al Hasan; Emon Mia; Md. Showkoth Akbor; Md. Tahajul Islam; Rokibul Islam Chowdhury; Md. Sabbir Hossain; Irfan Aamer Ansari; Siddique Akber Ansari; Md. Amirul Islam; Zainab M. Almarhoon; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Correction: Biosynthesis, Signaling, Homeostasis, Transport, and Regulatory Mechanisms of Cytokinin in Rice and Arabidopsis Response to Heat Stress - Md. Atik Mas-ud; Sadiya Arefin Juthee; Md. Rayhan Chowdhury; Md. Hosenuzzaman; Md. Firose Hossain; Randa Mohammed Zaki; Muhammad Fazle Rabbee; Mohammad Nurul Matin (Journal of Plant Growth Regulation, 2025)

Biosynthesis, Signaling, Homeostasis, Transport, and Regulatory Mechanisms of Cytokinin in Rice and Arabidopsis Response to Heat Stress - Md. Atik Mas-ud; Sadiya Arefin Juthee; Md. Rayhan Chowdhury; Md. Hosenuzzaman; Md. Firose Hossain; Randa Mohammed Zaki; Muhammad Fazle Rabbee; Mohammad Nurul Matin (Journal of Plant Growth Regulation, 2025)

Fabrication of hydroxyapatite-based scaffold and improvement of hardness by control addition of silica - Md. Kawcher Alam; Md. Sahadat Hossain; Muhammad Shahriar Bashar; Newaz Mohammed Bahadur; Samina Ahmed (Next Research, 2025)

The heat shock matters with specific attention to the expression of Hsp60 under thermal stress in fish: A critical review - Md Toasin Hossain Aunkor; Mohammad Mehedi Hasan Khan; Muhammad Anamul Kabir; Md Topu Raihan; Md Faruque Miah (Ecological Genetics and Genomics, 2025)

Combined effects of ternary oxides (Mg-Cu-O) and jute stick derived activated carbon for hydrogen storage in MgH2 - Mehedi Hasan; Deboshree Rani Mukta; Abdullah Mohammad Sarjish; Stefano Enzo; Muhammad Nurunnabi Siddiquee; Mohammad Mozahar Hossain; Victoria Padilla; Mohammed Jasim Uddin; Wasikur Rahman (Environmental Science and Pollution Research, 2025)

Learning-based estimation of cattle weight gain and its influencing factors - Muhammad Riaz Hasib Hossain; Rafiqul Islam; Shawn R. McGrath; Md Zahidul Islam; David Lamb (Computers and Electronics in Agriculture, 2025)

Combinatorial radiation-induced mutagenesis of Bacillus licheniformis and comparative whole genome sequencing to elucidate mutagenic effects on protease production - Jamila A. Tuly; Haile Ma; Hossain M. Zabed; Xianghui Qi; Muhammad Asif; Zhang Xinyan; Garba Betchem; Quaisie Janet (Food Bioscience, 2025)

Advancing low-trophic extractive mariculture (LTEM): Strategies for a thriving blue economy in Bangladesh - Md Asaduzzaman; Md Nahiduzzaman; Muhammad Tanvir Hossain Chowdhury; Md Moshiur Rahman; Abdullah-Al Mamun; Mohammad Mokarrom Hossain (Marine Policy, 2025)

Unmasking heavy metal contamination: Tracing, risk estimating and source fingerprinting from coastal sediments of the Payra River in Bangladesh - Salma Sultana; Niger Sultana; Mohammad Moniruzzaman; Muhammad Rehan Dastagir; Md Kamal Hossain (Marine Pollution Bulletin, 2025)

Corrigendum to ‘Trace element bioaccumulation in edible red seaweeds (Rhodophyta): A risk assessment for consumers’ [Environ. Pollut. 307 (2022) 1–10/119560] - Md Solaiman Hossain; Eurida Liyana; Saad Al-din Sifat; Fuad Ameen; Md Akram Ullah; Yeasmin Nahar Jolly; Shamshad Begum Quraishi; Mofazzal Hossain; Sazlina Salleh; Sharmin Akter; Mohammad Afzal Hossain; Muhammad Zobayer Bin Mukhlish; et al. (Environmental Pollution, 2025)

Installation and inclined loading of a suction caisson anchor in calcareous sand - Sunji Park; Muhammad Shazzad Hossain; Youngho Kim; Shah Neyamat Ullah; Yuxia Hu (Ocean Engineering, 2025)

Easing extraction of spudcan foundations through electrokinetic phenomenon - Yuri Sugiyama; Nagate Hashimoto; Daiki Takano; Muhammad Shazzad Hossain (Ocean Engineering, 2025)

Impact of synbiotic on growth performance, histo-architectural modulation of lymphoid organ, hematology, blood biochemistry and humoral immune response in naked neck chicken - Hemayet Hossain; Harimurti Nuradji; Mohammad Yousuf Miah; Muhammad Nazrul Islam; Md. Saiful Islam Siddiqui (Tropical Animal Health and Production, 2025)

Impact of dairy wastewater on paddy rice cultivation, leachate microbes, and soil health under alternate wetting and drying irrigation - Juli Akter; Md. Touhidul Islam; Nusrat Jahan; Mohammed Mizanur Rahman; M. G. Mostofa Amin; Muhammad Tofazzal Hossain; A. K. M. Adham (Paddy and Water Environment, 2025)

Impacts of natural and anthropogenic changes on the morphology and shoreline dynamics along the southeast coast of Bangladesh - Md Sakaouth Hossain; Muhammad Yasir; Zahidul Bari; Mahmuda Khatun; Maftuha Jahan (Arabian Journal of Geosciences, 2025)

Formation of particulate matter in the ambient air of Dhaka city, Bangladesh - Md. Yeasin Pabel; Md. Fakrul Islam; Muhammad Nurul Huda; Shahid Akhtar Hossain; M. Muhibur Rahman; Md. Mominul Islam (Air Quality, Atmosphere & Health, 2025)

Introduction of an optimised dynamic installation anchor via model test and numerical analysis: Freefall in the water column - Junsik Bae; Muhammad Shazzad Hossain; Youngho Kim (Ocean Engineering, 2024)

Removal of airborne particulate matter by evergreen tree species in Dhaka, Bangladesh - Saif Shahrukh; Richard Baldauf; Robert Popek; Mohammad Moniruzzaman; Muhammad Nurul Huda; Md. Mominul Islam; Shahid Akhtar Hossain; Mohammad Enayet Hossain (Environmental Pollution, 2024)

PPG2RespNet: a deep learning model for respirational signal synthesis and monitoring from photoplethysmography (PPG) signal - Md Nazmul Islam Shuzan; Moajjem Hossain Chowdhury; Saadia Binte Alam; Mamun Bin Ibne Reaz; Muhammad Salman Khan; M. Murugappan; Muhammad E. H. Chowdhury (Physical and Engineering Sciences in Medicine, 2024)

Genetic variation, population structure, and cluster analysis of rice (Oryza sativa L.) genotypes using morphological characteristics and molecular markers - Mst Fatamatuzzohora; Md. Sayeedul Islam; Muhammad Fazle Rabbee; Md. Shahadat Hossain; Sang Gu Kang; Mohammad Nurul Matin (Cereal Research Communications, 2024)

Mix and manage: Cultivar mixtures can maintain yield under high wheat blast disease pressure - Timothy J. Krupnik; Md. Harun-Or-Rashid; Dinabandhu Pandit; Rabiul Islam; Md. Khaled Hossain; José Mauricio Cunha Fernandes; Krishna Kanta Roy; Muhammad Rezaul Kabir; Sabine Stuerz; Pawan Kumar Singh; Golam Faruq (Crop Protection, 2024)

From farm to function: Exploring new possibilities with jute nanocellulose applications - Amjad Farooq; Syed Rashedul Islam; Md. Al-Amin; Mohammed Kayes Patoary; Md Tanjim Hossain; Muhammad Tauseef Khawar; Zongqian Wang; Mingwei Tian (Carbohydrate Polymers, 2024)

Microplastic pollution in aquatic ecosystem: A review of existing policies and regulations - Muhammad Tariq Khan; Sajid Rashid; Unzile Yaman; Saeed Ahsan Khalid; Asif Kamal; Mushtaq Ahmad; Nasrin Akther; Md Abul Kashem; Md Faysal Hossain; Wajid Rashid (Chemosphere, 2024)

Recent advances of MXene@MOF composites for catalytic water splitting and wastewater treatment approaches - Samreen Afzal; Aziz ur Rehman; Tayyaba Najam; Ismail Hossain; Mostafa A.I. Abdelmotaleb; Sundas Riaz; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Chemosphere, 2024)

Biosensor-assisted evolution of RhaD for enhancing the biosynthetic yield of d-allulose - Beini Chen; Xinrui Tang; Yufei Zhang; Hossain M. Zabed; Yuvaraj Ravikumar; Muhammad Waheed Iqbal; Jiayin Wang; Mei Zhao; Xianghui Qi (Food Bioscience, 2024)

Sediment management using bandal-like structures as nature-based solution - Md. Munsur Rahman; Shampa; Anisul Haque; Hajime Nakagawa; Hao Zhang; Ashiqur Rahman; Maruf Dustegir; Motaher Hossain; Muhammad Muktadir Hussain; Johurul Islam; Sudipta Kumar Hore (Environmental Fluid Mechanics, 2024)

Effect of padeye offset ratio on keying behaviours and capacity of square plate anchors in clay - Li Cheng; Fujun Niu; Muhammad S. Hossain; Qi Wang; Youngho Kim (Ocean Engineering, 2024)

An innovative interface friction algorithm for simulating dynamic installation of anchors using CEL approach - Junsik Bae; Youngho Kim; Muhammad Shazzad Hossain (Ocean Engineering, 2024)

Potential of repurposing decommissioned subsea flowlines to dynamically installed anchors - Muhammad Shazzad Hossain; Ming Hui Gao; Yuxia Hu; Scott Draper (Ocean Engineering, 2024)

Examining drinking water quality: analysis of physico-chemical properties and bacterial contamination with health implications for Shangla district, Khyber Pakhtunkhwa, Pakistan - Muhammad Salam; Dong Bo; Fakhri Alam; Islam Uddin; Md. Nuralam Hossain; Faisal Hayat; Waheed Ullah (Environmental Geochemistry and Health, 2024)

Evaluation of the potentials of rice varieties and water management practices for reducing human health risks associated with polluted river water irrigated rice in Bangladesh - Masahiro Tokumura; Jumpei Miyazaki; Mahmud Hossain; Anwar Hossain; Mohammad Raknuzzaman; Qi Wang; Yuichi Miyake; Takashi Amagai; Shigeki Masunaga; Shofiqul Islam; Muhammad Rafiqul Islam; Masakazu Makino (Science of The Total Environment, 2024)

Biomonitoring potentially toxic elements in atmospheric particulate matter of greater Dhaka region using leaves of higher plants - Zuairia Binte Jashim; Saif Shahrukh; Shahid Akhtar Hossain; Jahan-E-Gulshan; Muhammad Nurul Huda; Md. Mominul Islam; Mohammad Enayet Hossain (Environmental Monitoring and Assessment, 2024)

Natural Isatin Derivatives Against Black Fungus: In Silico Studies - Md. Saddam Hossain; Md. Anisur Rahman; Prithbey Raj Dey; Md. Parvez Khandocar; Md. Yeakub Ali; Mahajabin Snigdha; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (Current Microbiology, 2024)

Hydrogen from sewage sludge: Production methods, influencing factors, challenges, and prospects - Usman Khan; Muhammad Bilal; Hossain Md. Adil; Nnabodo Darlington; Ahsan Khan; Nouman Khan; I. Ihsanullah (Science of The Total Environment, 2024)

Quantifying canopy nitrogen of Aman rice utilizing multi-temporal unmanned aerial systems - Maruf Hossain; Hasan Muhammad Abdullah; Tanvir Ahmmed; Md Giashuddin Miah; Moin Us Salam; Majharul Islam; Md Mizanur Rahman (Remote Sensing Applications: Society and Environment, 2024)

Reservoir porosity assessment and anomaly identification from seismic attributes using Gaussian process machine learning - Maulana Hutama Rahma Putra; Maman Hermana; Ida Bagus Suananda Yogi; Touhid Mohammad Hossain; Muhammad Faris Abdurrachman; Said Jadid A. Kadir (Earth Science Informatics, 2024)
Porosity, as one of the reservoir properties, is an important parameter to numerous studies, i.e., the reservoir’s oil/gas volume estimation or even the storage capacity measurement in the Carbon Capture Storage (CCS) project. However, an approach to estimate porosity using elastic property from the inversion propagates its error, affecting the result’s accuracy. On the other hand, direct estimation from seismic data is another approach to estimating porosity, but it poses a high non-linear problem. Thus, we propose the non-parametric machine learning approach, Gaussian Process (GP), which draws distribution over the function to solve the high non-linear problem between seismic data with porosity and quantify the prediction uncertainty simultaneously. With the help of Random Forest (RF) as the feature selection method, the GP predictions show excellent results in the blind test, a well that is completely removed from the training data, and comparison with other machine learning models. The uncertainty, standard deviation from GP prediction, can act as a quantitative evaluation of the prediction result. Moreover, we generate a new attribute based on the quartile of the standard deviation to delineate the anomaly zones. High anomaly zones are highlighted and associated with high porosity from GP and low inverted P-impedance from inversion results. Thus, applying the GP using seismic data shows its potential to characterize the reservoir property spatially, and the uncertainty offers insights into quantitative and qualitative evaluation for hydrocarbon exploration and development.

Retraction Note: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md.Mominur Rahman; Md.Rezaul Islam; Sheikh Shohag; Md.Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md.Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md.Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2024)

Assessment of dietary polyvinylchloride, polypropylene and polyethylene terephthalate exposure in Nile tilapia, Oreochromis niloticus: Bioaccumulation, and effects on behaviour, growth, hematology and histology - Israt Jahan; Gourab Chowdhury; Saba Rafi; Md. Atique Ashab; Mukta Sarker; Ananya Chakraborty; Nicolas Couetard; Muhammad Anamul Kabir; Mohammad Amzad Hossain; Mohammed Mahbub Iqbal (Environmental Pollution, 2024)

Engineering of insecticidal hybrid gene into potato chloroplast genome exhibits promising control of Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - Md. Jakir Hossain; Allah Bakhsh; Faiz Ahmad Joyia; Emre Aksoy; Neslihan Zahide Özturk Gökçe; Muhammad Sarwar Khan (Transgenic Research, 2023)

Exploring the economic impact of institutional entrepreneurship, social Innovation, and poverty reduction on carbon footprint in BRICS countries: what is the role of social enterprise? - Fairtown Zhou Ayoungman; Abid Hossain Shawon; Rizwan Raheem Ahmed; Muhammad Kamran Khan; Md. Shoriful Islam (Environmental Science and Pollution Research, 2023)

Linking tourist's footprint and environmental tragedy through transportation, globalization and energy choice in BIMSTEC region: Directions for a sustainable solution using novel GMM-PVAR approach - Atif Jahanger; Mohammad Razib Hossain; Ashar Awan; Tomiwa Sunday Adebayo; Muhammad Zubair Chishti (Journal of Environmental Management, 2023)

Groundwater vulnerability assessment to pollution using GIS-based DRASTIC and GOD methods in Araihazar upazila of Narayanganj district, Bangladesh - Muhammad Abu Sayed; A.S.M. Maksud Kamal; Abrar Hossain; Mahmudul Hasan; Mahfuzur R Khan; Kazi Matin Uddin Ahmed; Peter S.K. Knappett (Groundwater for Sustainable Development, 2023)

Antiemetic effects of sclareol, possibly through 5-HT3 and D2 receptor interaction pathways: In-vivo and in-silico studies - Mehedi Hasan Bappi; Abdullah Al Shamsh Prottay; Khattab Al-Khafaji; Md Showkoth Akbor; Muhammad Kamal Hossain; Md Shahazul Islam; Afia Ibnath Asha; Cassio Rocha Medeiros; Catarina Martins Tahim; Elaine Cristina Pereira Lucetti; Henrique Douglas Melo Coutinho; Hossam Kamli; et al. (Food and Chemical Toxicology, 2023)

CIMCA: Infusing computational intelligence in multi-criteria analysis to assess groundwater potential for recharge - Rashed Uz Zzaman; Muhammad Ali Nayeem; Sara Nowreen; Imran Hossain Newton; AKM Saiful Islam; Anwar Zahid; M. Sohel Rahman (Environmental Modelling & Software, 2023)

Ranking Ship Detection Methods Using SAR Images Based on Machine Learning and Artificial Intelligence - Muhammad Yasir; Abdoul Jelil Niang; Md Sakaouth Hossain; Qamar Ul Islam; Qian Yang; Yuhang Yin (Journal of Marine Science and Engineering, 2023)
We aimed to improve the performance of ship detection methods in synthetic aperture radar (SAR) images by utilizing machine learning (ML) and artificial intelligence (AI) techniques. The maritime industry faces challenges in collecting precise data due to constantly changing sea conditions and weather, which can affect various maritime operations, such as maritime security, rescue missions, and real-time monitoring of water boundaries. To overcome these challenges, we present a survey of AI- and ML-based techniques for ship detection in SAR images that provide a more effective and reliable way to detect and classify ships in a variety of weather conditions, both onshore and offshore. We identified key features frequently used in the existing literature and applied the graph theory matrix approach (GTMA) to rank the available methods. This study’s findings can help users select a quick and efficient ship detection and classification method, improving the accuracy and efficiency of maritime operations. Moreover, the results of this study will contribute to advancing AI- and ML-based techniques for ship detection in SAR images, providing a valuable resource for the maritime industry.

Kinetic model derived from machine learning for accurate prediction of microalgal hydrogen production via conversion from low thermally pre-treated palm kernel expeller waste - Mohamad Zulfadhli Ahmad Sobri; Kuan Shiong Khoo; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sabah Ansar; Md Sohrab Hossain; Worapon Kiatkittipong; Chuxia Lin; Hui-Suan Ng; Juliana Zaini; Muhammad Roil Bilad; Man Kee Lam; et al. (Chemosphere, 2023)

Could climate change exacerbate droughts in Bangladesh in the future? - Mahfuzur Rahman; Md Sakib Hasan Tumon; Md Monirul Islam; Ningsheng Chen; Quoc Bao Pham; Kashif Ullah; Sumaiya Jarin Ahammed; Sharmina Naznin Liza; Md Abdul Aziz; Salit Chakma; Muhammad Esmat Enan; Md. Alomgir Hossain; et al. (Journal of Hydrology, 2023)

Morphological change assessment of a coastal island in SE Bangladesh reveal high accumulation rates - Md Sakaouth Hossain; Muhammad Yasir; Md. Shams Shahriar; Maftuha Jahan; Shanwei Liu; Abdoul Jelil Niang (Regional Studies in Marine Science, 2023)

Exploring the multifunctional roles of quantum dots for unlocking the future of biology and medicine - Muhammad Kashif Ali; Saher Javaid; Haseeb Afzal; Imran Zafar; Kompal Fayyaz; Qurat ul Ain; Mohd Ashraf Rather; Md. Jamal Hossain; Summya Rashid; Khalid Ali Khan; Rohit Sharma (Environmental Research, 2023)

Isolation of two new triterpene glycoside from the fruits of Terminalia arjuna and their in vitro and in silico studies - Rashadul Hossain; Rajia Sultana; Md. Din Islam; Shahed Zaman; Muhammad Iqbal Choudhary (Natural Product Research, 2023)

Frugal innovation as a source of sustainable entrepreneurship to tackle social and environmental challenges - Muhammad Shehryar Shahid; Mokter Hossain; Subhan Shahid; Tehreem Anwar (Journal of Cleaner Production, 2023)

An assessment of rural household vulnerability and resilience in natural hazards: evidence from flood prone areas - Shah Fahad; Mohammad Shakhawat Hossain; Nguyen Thi Lan Huong; Abdelmohsen A. Nassani; Mohamed Haffar; Muhammad Rashid Naeem (Environment, Development and Sustainability, 2023)

Municipal solid waste treatment for bioenergy and resource production: Potential technologies, techno-economic-environmental aspects and implications of membrane-based recovery - Naila Amin; Muhammad Aslam; Zakir khan; Muhammad Yasin; Shakhawat Hossain; Muhammad Kashif Shahid; Abrar Inayat; Ahmed Samir; Rizwan Ahmad; Mohammad N. Murshed; Muhammad Shahzad Khurram; Mohamed E. El Sayed; et al. (Chemosphere, 2023)

Instance segmentation ship detection based on improved Yolov7 using complex background SAR images - Muhammad Yasir; Lili Zhan; Shanwei Liu; Jianhua Wan; Md Sakaouth Hossain; Arife Tugsan Isiacik Colak; Mengge Liu; Qamar Ul Islam; Syed Raza Mehdi; Qian Yang (Frontiers in Marine Science, 2023)
It is significant for port ship scheduling and traffic management to be able to obtain more precise location and shape information from ship instance segmentation in SAR pictures. Instance segmentation is more challenging than object identification and semantic segmentation in high-resolution RS images. Predicting class labels and pixel-wise instance masks is the goal of this technique, which is used to locate instances in images. Despite this, there are now just a few methods available for instance segmentation in high-resolution RS data, where a remote-sensing image’s complex background makes the task more difficult. This research proposes a unique method for YOLOv7 to improve HR-RS image segmentation one-stage detection. First, we redesigned the structure of the one-stage fast detection network to adapt to the task of ship target segmentation and effectively improve the efficiency of instance segmentation. Secondly, we improve the backbone network structure by adding two feature optimization modules, so that the network can learn more features and have stronger robustness. In addition, we further modify the network feature fusion structure, improve the module acceptance domain to increase the prediction ability of multi-scale targets, and effectively reduce the amount of model calculation. Finally, we carried out extensive validation experiments on the sample segmentation datasets HRSID and SSDD. The experimental comparisons and analyses on the HRSID and SSDD datasets show that our model enhances the predicted instance mask accuracy, enhancing the instance segmentation efficiency of HR-RS images, and encouraging further enhancements in the projected instance mask accuracy. The suggested model is a more precise and efficient segmentation in HR-RS imaging as compared to existing approaches.

Amentoflavone derivatives significantly act towards the main protease (3CLPRO/MPRO) of SARS-CoV-2: in silico admet profiling, molecular docking, molecular dynamics simulation, network pharmacology - Dipta Dey; Rajib Hossain; Partha Biswas; Priyanka Paul; Md. Aminul Islam; Tanzila Ismail Ema; Bibhuti Kumar Gain; Mohammad Mehedi Hasan; Shabana Bibi; Muhammad Torequl Islam; Md. Ataur Rahman; Bonglee Kim (Molecular Diversity, 2023)

Recent scenario and nexus between natural resource dependence, energy use and pollution cycles in BRICS region: Does the mediating role of human capital exist? - Atif Jahanger; Mohammad Razib Hossain; Muhammad Usman; Joshua Chukwuma Onwe (Resources Policy, 2023)

Phenotypic and Genotypic Analysis of the Population of Phytophthora infestans in Bangladesh Between 2014 and 2019 - Md. Huzzatul Islam; Sangee Sarkar Shanta; Muhammad Iqbal Hossain; Muhammed Ali Hossain; Md. Monower Hossain; Ebna Habib Md. Shofiur Rahaman; Abdullah Al Mahmud; Md. Abdullah Yousuf Akhond; Louise Sullivan; David E. L. Cooke; Geert J. T. Kessel; Louise R. Cooke; et al. (Potato Research, 2023)
In Bangladesh, the third largest producer of potatoes in Asia, late blight, caused by Phytophthora infestans , is the major constraint to production. Nevertheless, there is a lack of published information on the pathogen population. A collection of 69 isolates obtained from samples of infected potato foliage collected in 2018–2019 varied significantly in their aggressiveness to detached potato leaflets and tuber slices of cv. Diamant. On leaflets, most isolates were highly aggressive, colonizing more than half the surface in 7 days. On tuber slices, while some isolates were highly aggressive, those collected in 2019 were less so. There was a significant effect of the locations from which the isolates were obtained on aggressiveness to both leaflets and tuber slices, but aggressiveness to leaflets and to tuber slices was not significantly correlated. All isolates were A2 mating type and either intermediate (38%) or resistant (62%) in sensitivity to the fungicide metalaxyl . A subset of 24 isolates all had mitochondrial DNA haplotype Ia. Samples of P. infestans DNA (124) from infected potato foliage obtained from Bangladesh (2014–2019) were genotyped by 12-plex SSR. The vast majority (95%) were assigned to EU_13_A2, which was present in every year in which samples were collected. Numerous EU_13_A2 variants were identified, many specific to Bangladesh. Six samples (from 2017 to 2019) had genotypes distinct from EU_13_A2 and with no close match to known European lineages. It is concluded that the current P. infestans population of Bangladesh is dominated by the aggressive lineage EU_13_A2, also dominant in India and Pakistan. The implications of this for control of late blight are discussed.

Personal protective equipment (PPE) disposal during COVID-19: An emerging source of microplastic and microfiber pollution in the environment - Muhammad Tariq Khan; Izaz Ali Shah; Md Faysal Hossain; Nasrin Akther; Yanbo Zhou; Muhammad Sajawal Khan; Muayad Al-shaeli; Muhammad Suleman Bacha; Ihsanullah Ihsanullah (Science of The Total Environment, 2023)

Enhancing the antibacterial activity of Lactobacillus reuteri against Escherichia coli by random mutagenesis and delineating its mechanism - Enyun Ma; Yingfeng An; Guoyan Zhang; Mei Zhao; Muhammad Waheed Iqbal; Hossain M. Zabed; Xianghui Qi (Food Bioscience, 2023)

Reduced tillage and crop diversification can improve productivity and profitability of rice-based rotations of the Eastern Gangetic Plains - Muhammad Arshadul Hoque; Mahesh K. Gathala; Jagadish Timsina; Md.A.T.M. Ziauddin; Mosharraf Hossain; Timothy J. Krupnik (Field Crops Research, 2023)

Multi-scale ship target detection using SAR images based on improved Yolov5 - Muhammad Yasir; Liu Shanwei; Xu Mingming; Sheng Hui; Md Sakaouth Hossain; Arife Tugsan Isiacik Colak; Dawei Wang; Wan Jianhua; Kinh Bac Dang (Frontiers in Marine Science, 2023)
Synthetic aperture radar (SAR) imaging is used to identify ships, which is a vital task in the maritime industry for managing maritime fisheries, marine transit, and rescue operations. However, some problems, like complex background interferences, various size ship feature variations, and indistinct tiny ship characteristics, continue to be challenges that tend to defy accuracy improvements in SAR ship detection. This research study for multiscale SAR ships detection has developed an upgraded YOLOv5s technique to address these issues. Using the C3 and FPN + PAN structures and attention mechanism, the generic YOLOv5 model has been enhanced in the backbone and neck section to achieve high identification rates. The SAR ship detection datasets and AirSARship datasets, along with two SAR large scene images acquired from the Chinese GF-3 satellite, are utilized to determine the experimental results. This model’s applicability is assessed using a variety of validation metrics, including accuracy, different training and test sets, and TF values, as well as comparisons with other cutting-edge classification models (ARPN, DAPN, Quad-FPN, HR-SDNet, Grid R-CNN, Cascade R-CNN, Multi-Stage YOLOv4-LITE, EfficientDet, Free-Anchor, Lite-Yolov5). The performance values demonstrate that the suggested model performed superior to the benchmark model used in this study, with higher identification rates. Additionally, these excellent identification rates demonstrate the recommended model’s applicability for maritime surveillance.

Foliar application of silicon-based nanoparticles improve the adaptability of maize (Zea mays L.) in cadmium contaminated soils - Sarfraz Ahmed; Muhammad Iqbal; Zahoor Ahmad; Muhammad Aamir Iqbal; Arkadiusz Artyszak; Ayman E. L. Sabagh; Hesham F. Alharby; Akbar Hossain (Environmental Science and Pollution Research, 2023)

Coupling of deep learning and remote sensing: a comprehensive systematic literature review - Muhammad Yasir; Wan Jianhua; Liu Shanwei; Hui Sheng; Xu Mingming; Md Hossain (International Journal of Remote Sensing, 2023)

REEs enriched heavy minerals from the river and beach sands of Bangladesh - Md Sakaouth Hossain; Azizur Rahman; Md. Shams Shahriar; Zahidul Bari; Muhammad Yasir (Arabian Journal of Geosciences, 2023)

Farmers’ climate change risk perception, adaptation capacity and barriers to adaptation: a multi-method approach - Muhammad Humayun Kabir; Kh. Zulfikar Hossain; Md. Javed Azad; Mou Leong Tan (Journal of Environmental Studies and Sciences, 2022)

Win-win: designing dual-use in climate projects for effective anti-corruption in Bangladesh - Mushtaq Khan; Mitchell Watkins; Salahuddin Aminuzzaman; Sumaiya Khair; Muhammad Zakir Hossain Khan (Climate and Development, 2022)

High prevalence of vancomycin non-susceptible and multi-drug resistant enterococci in farmed animals and fresh retail meats in Bangladesh - Mohammed A. Samad; Md Shahjalal Sagor; Muhammad Sazzad Hossain; Md Rezaul Karim; Mohammad Asheak Mahmud; Md Samun Sarker; Fahria A. Shownaw; Zakaria Mia; Roderick M. Card; Agnes Agunos; Lindahl Johanna (Veterinary Research Communications, 2022)

Development of early flowering, short life-spanned jute (Corchorus spp.) mutant via ethyl methane sulfonate mutagenesis - Quazi Md. Mosaddeque Hossen; S. M. Badier Rahman; Md. Nazibur Rahman; Muhammad Delwar Hossain Sarker; Md. Moniruzzaman; Md. Zablul Tareq; Md. Abu Sadat; Kazi Md. Yasin Arafat; Md. Sarwar Jahan; Md. Samiul Haque (Journal of Crop Science and Biotechnology, 2022)

A comprehensive review of heavy metal pollution in the coastal areas of Bangladesh: abundance, bioaccumulation, health implications, and challenges - Md.Refat Jahan Rakib; Md. Asrafur Rahman; Amarachi Paschaline Onyena; Rakesh Kumar; Aniruddha Sarker; M. Belal Hossain; Abu Reza Md. Towfiqul Islam; Md. Saiful Islam; Md. Mostafizur Rahman; Yeasmin Nahar Jolly; Abubakr M. Idris; Mir Mohammad Ali; et al. (Environmental Science and Pollution Research, 2022)

Rep-PCR Analyses Reveal Genetic Variation of Ralstonia solanacearum Causing Wilt of Solanaceaous Vegetables in Bangladesh - Md. Mosharraf Hossain; Md. Mostafa Masud; Muhammad Iqbal Hossain; Mohammad Mahbubul Haque; Mohammad Sharif Uddin; Md. Zahangir Alam; Md. Rashidul Islam (Current Microbiology, 2022)

Correction to: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Clearance of Escherichia coli by the freshwater mussel Lamellidens marginalis in laboratory conditions - Md. Firoz Shah; Md. Abdullah Al Mamun; Muhammad Tofazzal Hossain; Mohammad Moniruzzaman; Selina Yeasmine; Md. Helal Uddin; M. Jasim Uddin (Molluscan Research, 2022)

Daytime and Nighttime Sea Surface Temperature (SST) along with Diurnal Variability (D-SST) in the Northern Bay of Bengal: A Remote Sensing Approach - Md Shahin Hossain Shuva; Md Rony Golder; Muhammad Abdur Rouf; Mohammad Muslem Uddin; Joyanta Bir (Thalassas: An International Journal of Marine Sciences, 2022)

Self-healing concrete for sustainable buildings. A review - Md. Riad Hossain; Rabeya Sultana; Muhammad Mainuddin Patwary; Noel Khunga; Pankaj Sharma; Sebastian Joya Shaker (Environmental Chemistry Letters, 2022)

Application of Biofloc Technology for the culture of Heteropneustes fossilis (Bloch) in Bangladesh: stocking density, floc volume, growth performance, and profitability - Md Shamsuddin; M. Belal Hossain; Moshiur Rahman; Mst. Salamun Kawla; Md. Badiul Alam Shufol; Muhammad Mamunur Rashid; Md. Asadujjaman; Md. Refat Jahan Rakib (Aquaculture International, 2022)

Current trends in polymerase chain reaction based detection of three major human pathogenic vibrios - Sharmin Quazi Bonny; M. A. Motalib Hossain; Syed Muhammad Kamal Uddin; Thiruchelvi Pulingam; Suresh Sagadevan; Mohd Rafie Johan (Critical Reviews in Food Science and Nutrition, 2022)

Authentication of Halal and Kosher meat and meat products: Analytical approaches, current progresses and future prospects - M. A. Motalib Hossain; Syed Muhammad Kamal Uddin; Sharmin Sultana; Yasmin Abdul Wahab; Suresh Sagadevan; Mohd Rafie Johan; Md. Eaqub Ali (Critical Reviews in Food Science and Nutrition, 2022)

Genomic attributes and recent advances in detection of white spot syndrome virus in shrimp: a review - Md Nazmul Hossain; Tanjia Afrin Chowdhury; Mahmudul Hasan; Kazi Faizul Azim; Sayadatunnasa Jenny; Muhammad Fazle Rabbee; Md. Mahbubur Rahman; Saneya Risa Somana (Marine Biology Research, 2021)

Energy, emission, profitability, and sustainability analyses of a grid-connected solar power plant proposed in airport sites of Bangladesh: a case study - Hemal Chowdhury; Tamal Chowdhury; Nazia Hossain; Piyal Chowdhury; Jefferson dos Santos Mascarenhas; Muhammad Mostafa Kamal Bhuiya (Environmental Science and Pollution Research, 2021)

Chlorophyll-a, SST and particulate organic carbon in response to the cyclone Amphan in the Bay of Bengal - Md Rony Golder; Md Shahin Hossain Shuva; Muhammad Abdur Rouf; Mohammad Muslem Uddin; Sayeda Kamrunnahar Bristy; Joyanta Bir (Journal of Earth System Science, 2021)

Short targeting multiplex PCR assay to detect and discriminate beef, buffalo, chicken, duck, goat, sheep and pork DNA in food products - Syed Muhammad Kamal Uddin; M. A. Motalib Hossain; Zaira Zaman Chowdhury; Mohd Rafie Bin Johan (Food Additives & Contaminants: Part A, 2021)

Evaluation of elite bread wheat lines for resistance to blast disease in Bangladesh - Krishna Kanta Roy; Md Mostofa Ali Reza; Md Muzahid-E-Rahman; Md Babul Anwar; Kishowar-E-Mustarin; Muhammad Rezaul Kabir; Paritosh Kumar Malaker; Naresh Chandra Deb Barma; Md Israil Hossain; Xinyao He; Aakash Chawade; Pawan Kumar Singh (Euphytica, 2021)

Toxic element profile of ice cream in Bangladesh: a health risk assessment study - Palash Kumar Dhar; Arifa Naznin; Muhammad Sarwar Hossain; Md. Kamrul Hasan (Environmental Monitoring and Assessment, 2021)

Employing social vulnerability index to assess household social vulnerability of natural hazards: an evidence from southwest coastal Bangladesh - Anjum Tasnuva; Md. Riad Hossain; Roquia Salam; Abu Reza Md. Towfiqul Islam; Muhammad Mainuddin Patwary; Sobhy M. Ibrahim (Environment, Development and Sustainability, 2021)

Nutritional Value, Phytochemical Profile, Antioxidant Property and Agar Yielding Potential of Macroalgae from Coasts of Cox’s Bazar and St. Martin’s Island of Bangladesh - Md. Tahmeed Hossain; Abdullah Al Mamun Sohag; Md. Nazmul Haque; Md. Tahjib-Ul-Arif; Raju Dash; Muhammad Tanvir Hossain Chowdhury; Md. Afzal Hossain; Il Soo Moon; Md. Abdul Hannan (Journal of Aquatic Food Product Technology, 2021)

Hydropower development along the major rivers basins in South Asia: benefits for Bangladesh - Muhammad Mizanur Rahaman; Mohammad Safayat Hossain (Sustainable Water Resources Management, 2020)

Exploring Water Consumption in Dhaka City Using Instrumental Variables Regression Approaches - Muhammad Shahadat Hossain Siddiquee; Raihan Ahamed (Environmental Processes, 2020)
This paper explores water consumption in Dhaka city for better understanding of its usage, and considers the implications of findings from distributive rationale. Using 459 household survey data collected by BRAC Institute of Governance and Development (BIGD), this study estimates income elasticities of water consumption after controlling the effects of other covariates including wealth-proxies, location, household size, water bill and spatial zones using the instrumental variable regression (IVREG) and instrumental variable quantile regression (IVQREG) approaches. The latter has an additive advantage over the former as the IVQREG provides a more accurate picture of the relationship of water consumption with the income throughout the entire water consumption distribution. Using the fixed pay variable as instrument, findings reveal the strong evidence that income is endogenous. The IVQREG results show that income elasticities are heterogeneous and vary significantly across the water quantiles, implying inequality in water consumption. It also provides strong systematic evidence as income elasticity of water consumption decreases with the increase in percentile. Significant spatial inequality in water consumption from IVREG approach disappears as we use IVQREG. This also strongly supports the systematic evidence obtained. Therefore, it is imperative to introduce different tariff structures among different water consumer groups for bringing equity in water consumption and revenue generation. However, Dhaka Water Supply & Sewerage Authority (DWASA) must ensure smart water meter before implementing such tariff structure as we face severe challenges while measuring residential water consumption.

Predicting the non-carcinogenic health hazards associated with emissions from developing coal-fired power plants in Payra, Bangladesh - Mashiat Hossain; Tanvir Ahmed; Muhammad Ashraf Ali (Air Quality, Atmosphere & Health, 2020)

Copper-induced oxidative stress, initiation of antioxidants and phytoremediation potential of flax (Linum usitatissimum L.) seedlings grown under the mixing of two different soils of China - Muhammad Hamzah Saleem; Shah Fahad; Shahid Ullah Khan; Mairaj Din; Abid Ullah; Ayman EL Sabagh; Akbar Hossain; Analía Llanes; Lijun Liu (Environmental Science and Pollution Research, 2020)

Comparison Study of Allelochemicals and Bispyribac-Sodium on the Germination and Growth Response of Echinochloa crus-galli L. - Sheikh Muhammad Masum; Mohammad Amzad Hossain; Hikaru Akamine; Jun-Ichi Sakagami; Takahiro Ishii; Toshihiro Konno; Ichiro Nakamura (Journal of Plant Growth Regulation, 2019)

Universal mitochondrial 16s rRNA biomarker for mini-barcode to identify fish species in Malaysian fish products - M. A. Motalib Hossain; Syed Muhammad Kamal Uddin; Zaira Zaman Chowdhury; Sharmin Sultana; Mohd Rafie Johan; Abdul Rohman; Yuny Erwanto; Md. Eaqub Ali (Food Additives & Contaminants: Part A, 2019)

Tropical hilsa shad ( Tenualosa ilisha ): Biology, fishery and management - M. Shahadat Hossain; S. M. Sharifuzzaman; Muhammad Abdur Rouf; Robert S. Pomeroy; Md Delwer Hossain; Sayedur R. Chowdhury; Sheikh AftabUddin (Fish and Fisheries, 2019)
Tropical hilsa shad, which is an anadromous fish migrating from the sea to spawn in freshwater river, constitutes an important fishery in some Asian and Middle East countries, particularly in Bangladesh. But, historical information on hilsa biology and ecology has confronted the scientists and policymakers with research and management challenges. We have reviewed both the old and recent findings on hilsa fishery to document the status of knowledge and potential gaps, necessary to comprehend for formulating a more effective fishery management plan. Thus, there has been a decline in hilsa catches in the riverine system associated with shift in fish migration routes, indiscriminate harvesting of brood and juvenile fish, and degradation of habitat. Specifically, the riverine hilsa catches peaked in the 1960s, declining thereafter, and became relatively abundant in marine waters since 1990s. Biological data indicated that hilsa goes through multiple reproductive cycles; therefore, a comprehensive understanding of reproductive biology, recruitment by various cohorts, stock abundance and habitats across the life cycle are necessary to accurately impose fishery regulatory measures, such as fishing ban in spawning season in Bangladesh. Moreover, domestication initiative is important for artificial seed production and mariculture development of hilsa that can not only offer economic return to small‐scale farmers but also reduce the growing pressure on capture fishery. Importantly, the arrangement of co‐management is found ideal as fishermen, scientists and managers can work jointly to improve the regulatory processes and to sustain the hilsa fishery over time.

Numerical simulation of caisson installation and dissipation in kaolin clay and calcareous silt - Kai Xiang Koh; Dong Wang; Muhammad Shazzad Hossain (Bulletin of Engineering Geology and the Environment, 2018)

Species-specific detection of Vibrio alginolyticus in shellfish and shrimp by real-time PCR using the groEL gene - Raju Ahmed; S. M. Rafiquzaman; Muhammad Tofazzal Hossain; Jong-Min Lee; In-Soo Kong (Aquaculture International, 2016)

Methyl jasmonate enhances phlorotannin production in the brown seaweed Ecklonia cava - Muhammad Tanvir Hossain Chowdhury; Ji-Young Cho; Dong-Hyun Ahn; Yong-Ki Hong (Journal of Applied Phycology, 2015)

Accumulation of phlorotannins in the abalone Haliotis discus hannai after feeding the brown seaweed Ecklonia cava - Issa Bangoura; Muhammad Tanvir Hossain Chowdhury; Ji-Young Kang; Ji-Young Cho; Je-Cheon Jun; Yong-Ki Hong (Journal of Applied Phycology, 2014)

Erratum to: Signaling Pathways Involved in 1-Octen-3-ol-Mediated Neurotoxicity in Drosophila melanogaster: Implication in Parkinson’s Disease - Arati A. Inamdar; Prakash Masurekar; Muhammad Hossain; Jason R. Richardson; Joan W. Bennett (Neurotoxicity Research, 2014)

Signaling Pathways Involved in 1-Octen-3-ol-Mediated Neurotoxicity in Drosophila melanogaster: Implication in Parkinson’s Disease - Arati A. Inamdar; Prakash Masurekar; Muhammad Hossain; Jason R. Richardson; Joan W. Bennett (Neurotoxicity Research, 2014)

Detection of Vibrio cholerae and Vibrio vulnificus by duplex PCR specific to the groEL gene - Muhammad Tofazzal Hossain; Yu-Ri Kim; Eun-Young Kim; Jong-Min Lee; In-Soo Kong (Fisheries Science, 2013)

A brown alga Sargassum fulvellum facilitates neuronal maturation and synaptogenesis - Md. Abdul Hannan; Ji-Young Kang; Yong-Ki Hong; HyunSook Lee; Muhammad Tanvir Hossain Chowdhury; Jae-Suk Choi; In Soon Choi; Il Soo Moon (In Vitro Cellular & Developmental Biology - Animal, 2012)

Salt effect of nisin Z isolated from a marine fish on the growth inhibition of Streptococcus iniae, a pathogen of streptococcosis - Won-Seok Heo; Eun-Young Kim; Yu-Ri Kim; Muhammad Tofazzal Hossain; In-Soo Kong (Biotechnology Letters, 2012)

Urban and peri-urban aquaculture as an immediate source of food fish: Perspectives of Dhaka City, Bangladesh - MD. Shahidul Islam; Muhammad Tanvir Hossain Chowdhury; MD. Mokhlesur Rahman; MD. Anwar Hossain (Urban Ecosystems, 2004)